Economic and organizational principles of implementing digital platforms into the development project management system - Ratnikov, D.; Krychevskyi, O.; Storozhuk, O.; Rotov, O.; Sheremet , D. (Ways to Improve Construction Efficiency, 2022)
The article examines the issue of operational adaptation of construction enterprises to the conditions of digital modernization, which emerges as a key factor in enhancing their competitiveness and resilience in a dynamic environment. Emphasis is placed on combining economic and organizational aspects of digital transformation, manifested in the transition from traditional management models to integrated digital platforms focused on efficient resource, risk, and business process management. From an economic perspective, the authors substantiate that the implementation of BIM, ERP, monitoring systems, and intelligent analytics forms a new cost and revenue structure, optimizes the life cycle of construction projects, reduces transaction costs, and strengthens investment predictability. Particular attention is paid to modern methodologies for assessing the effectiveness of digital solutions — MCDA, Balanced Scorecard, CVaR, TCO/LCC, Digital Maturity Models, and ESG approaches — considered as tools for multidimensional diagnostics of innovation performance in the development business. The organizational aspect is revealed through the analysis of management structure transformation, the introduction of flexible models such as Integrated Project Delivery (IPD) and Agile, the development of employees’ digital competencies, the improvement of communication quality, and the creation of conditions for transparent stakeholder interaction within a unified information environment. The practical example of KAN Development illustrates the advantages of digital adaptation: reduction of costs and risks through the implementation of ERP and BIM, the formation of a new corporate culture through digital collaboration, and an increase in customer value through Smart Building Management and digital services. In conclusion, it is demonstrated that digital modernization is not only a technical innovation but also a strategic foundation for shaping a new logic of construction enterprise management, ensuring their flexibility, transparency, and competitiveness in the context of global transformations.